Integral health assistance: a look to physiotherapy from the point of view of the Family Health Team - Marcio Costa de Souza; Thamyres Menezes de Araújo; Wanderley Matos Reis Júnior; Jairrose Nascimento Souza; Alba Benemérita Alves Vilela; Túlio Batista Franco (O Mundo da Saúde)
Integral health assistance as a principle of Brazil’s Unified Health System aims to guarantee the individual a health care service that go beyond healing practice and focus the individual at all levels of assistance and considering the subject inserted into a social context, a family and a culture. To reorient the structure of the Health Care System, the government consolidated the Family Health Strategy, composed by a multidisciplinary team of professionals engaged in the search for a humane and collective health care that provides quality of life for the population. Therefore, the tasks of physiotherapy are particularly linked to the actions of Public Health, justifying thus the need for its inclusion in the Family Health Team. This research aims to analyze the understanding of the Family Health Team regarding integral care in the National Health System, as well as the design team on physiotherapy in primary health care. The study is qualitative, conducted by applying semi-structured interviews to 12 professionals which are members of the Family Health Team in a city of Bahia state. We concluded that some changes are needed so that integral health assistance may be a reality in health care. In this context, it is imperative the work of physical therapists in the Family Health Strategy.